IMPLICATIONS OF MUHAMMAD IQBAL'S THINKING ON ISLAMIC RELIGIOUS EDUCATION AND CHARACTERISTICS - Fathirah, Annisaul; Abu Bakar, M. Yunus (Nurul Jadid University, Paiton Probolinggo, East Java, 2021)
AbstractIslamic Religious Education with all that is related to it is knowledge that only becomes a theory when it is not applied. Muhammad Iqbal is figures who reconstructed Islamic religious education and western education were able to run simultaneously which would create a perfect human being. The theory created by Muhammad Iqbal in this journal will be applied to students through”the subjects of Islamic Religious Education and character using learning methods that are in accordance with the curriculum,”both regarding the objectives, scope, field conditions, so that an educational atmosphere can be realized in accordance with the values Islam.